Following Consistency of Energy-Saving Operation for Urban Rail Trains Based on Event Triggering Mechanism. (8th December 2022) - Xu, Ruxun; Meng, Jianjun; Zhang, Juhui; Chen, Xiaoqiang; Li, Decang
Abstract : To reduce the traction energy consumption of urban rail trains by regenerating energy, a train traction and braking model was designed based on algebraic graph theory and train dynamics theory and the following consistency model of energy-saving operation of urban rail trains was constructed based on the conditions of the coordination coefficient and the operating condition conversion of trains. Not only to constantly update the consistency controller and save communication resources but also to optimize the energy-saving effect, the consistency algorithm of event triggering was used to search for the optimal operating conditions of trains and the energy-saving operation scheme for multiple trains was established. Taking the train diagram of a subway line in Jinan as an example, the energy-saving control scheme of four trains was solved by MATLAB simulation. The simulation results show that the model can not only ensure parking accuracy and punctuality but also energy savings effectively; that is, the proportion of the total regenerative energy used by the follower train in the actual energy consumption is increased from 3.32% to 10.76%, and the actual total energy consumption of the train is reduced by 9.23%.